Capability and Development of Paying Waste Management towards Rumid Environmental Improvement in Palembang City Growth Centre - Imelda Imelda; Feny Marissa; Deassy Apriani (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2019)
This research was carried out in the slum area located in the sub-district as the growth center of Palembang City, namely Ilir Timur II Subdistrict and secondary growth center, Ilir Barat District II. The analytical method used is the analysis of the Contingent Valuation Method (CVM), and the data used are primary data and secondary data. Public perceptions of participatory waste management efforts to improve environmental quality in slums are relatively good. It can be seen that as much as 61 percent of respondents answered that the people responsible for waste management were the people themselves. The level of public acceptance of participatory waste management efforts to improve the quality of the environment in slums is quite good. 120 people or 80 percent of respondents are willing to pay for waste management. Of the 120 respondents, the amount of rupiah willing to be paid to manage waste is Rp. 1,358,000. With monthly waste management fees of IDR 5,000-10,000, - Factors that influence the amount of willingness to pay for waste management, namely waste volume has a positive and significant effect, while income, education level, and number of dependents have no significant effect. Likewise with gender, between men and women does not have a significant effect so there is no difference in influence. The types of jobs between formal and informal, locations according to the primary, secondary and tertiary growth center categories and slum characteristics also have different effects on willingness to pay for waste management